On the Fringe: Where Science Meets Pseudoscience by Michael D. Gordin: Essay Review: Speaking of "Pseudo-Science" Entails Scientism: The Importance of Not Being Earnest about Science - Bauer, Henry (Journal of Scientific Exploration, 2022)
In contemporary society, “science” signifies authoritative understanding of the natural world; therefore “pseudo”-science means claimed but inauthentic, false knowledge about nature; and “fringe” science, between those two, means doubtfully trustworthy knowledge. In any case, whether or not it is a conscious decision and whether or not it is admitted, attributing authoritative understanding to science entails accepting the religion of scientism, the belief that scientific knowledge is superior to any other claims of knowledge. But the content of “science” is created by human beings. Once it is conceded that science is fallible, as all human activities are bound to be, it becomes clear that any mainstream “scientific consensus” is also fallible; and therefore heterodox claims of knowledge should be greeted, initially at least, with a degree of tolerance and a willingness to consider evidence, to seek objective facts before judging something to be false knowledge, or, in contemporary jargon, “fake news.” The subtitle of this essay was inspired by the life (and work) of Oscar Wilde, who was only one among an uncountable host of human beings who have suffered seriously from the intolerance of their fellow human beings, the intolerance of the societies in which they lived. The intolerance Wilde faced may have had nothing directly to do with science, but it did indirectly: Declaring and believing his sexual preferences to be “unnatural” and therefore abhorrent presumed, with great dogmatic earnestness, that we command authentic knowledge about what is natural.